الفيلم الإلكتروني في تعليم الحوار بالمدرسة الثانوية - Nur Hasaniyah; Ummul Hamidah Wilayati; Rizki Fathul Huda (Kalimatuna: Journal of Arabic Research, 2022)
This study seeks to show students' abilities after utilizing the cartoon film medium to improve their dialogue skills in 10th grade students at Bekasi First Governmental Islamic High School, as well as to compare the results of the cartoon film media to the traditional technique. This study employs experimental research with a quantitative methodology, as well as the creation of a real-world experiment (one group, pre-test and post-test). The effectiveness of students' acquisition of dialogue skills development, understanding the content of dialogues, and learning outcomes in dialogue skill appeared after utilizing the cartoon video at a school. There is a significant difference between the pre-test and post-test, indicating that using the cartoon film method to teach conversation to pupils is quite effective.